Investigating the influence of collagen cross-linking on mechanical properties of thoracic aortic tissue - Lee, Chung Won; Lee, Chiseung; Baek, Seungik; Akkoyun, Emrah; Ryu, Dongman (Frontiers in Bioengineering and Biotechnology, 2024)
Vascular diseases, such as abdominal aortic aneurysms, are associated with tissue degeneration of the aortic wall, resulting in variations in mechanical properties, such as tissue ultimate stress and a high slope. Variations in the mechanical properties of tissues may be associated with an increase in the number of collagen cross-links. Understanding the effect of collagen cross-linking on tissue mechanical properties can significantly aid in predicting diseased aortic tissue rupture and improve the clarity of decisions regarding surgical procedures. Therefore, this study focused on increasing the density of the aortic tissue through cross-linking and investigating the mechanical properties of the thoracic aortic tissue in relation to density. Uniaxial tensile tests were conducted on the porcine thoracic aorta in four test regions (anterior, posterior, distal, and proximal), two loading directions (circumferential and longitudinal), and density increase rates (0-12%). As a result, the PPC (Posterior/Proximal/Circumferential) group experienced a higher ultimate stress than the PDC (Posterior/Distal/Circumferential) group. However, this relationship reversed when the specimen density exceeded 3%. In addition, the ultimate stress of the ADC (Anterior/Distal/Circumferential) and PPC group was greater than that of the APC (Anterior/Proximal/Circumferential) group. However, these findings reversed when the specimen density exceeded 6% and 9%, respectively. Finally, the high slope of the PDL (Posterior/Distal/Longitudinal) group was lower than that of the ADL (Anterior/Distal/Longitudinal) group, but the high slope of the PDL group appeared larger due to the stabilization treatment. This highlights the potential impact of density variations on the mechanical properties of specific specimen groups.